Transcranial sonography findings in a large family with homozygous and heterozygous PINK1 mutations. Issue 9 (9th May 2008) - Hagenah, J M; Becker, B; Brüggemann, N; Djarmati, A; Lohmann, K; Sprenger, A; Klein, C; Seidel, G
Abstract : Objective: To investigate substantia nigra (SN) echogenicity in members of a family with homozygous and heterozygous PTEN induced kinase ( PINK1 ) mutations with or without signs of Parkinson's disease (PD). Methods: Transcranial sonography (TCS) was used to investigate 20 members of a family with PINK1 mutations, including four homozygous and 11 heterozygous mutation carriers and five individuals with no mutation. For comparison, a healthy control group of 18 subjects without a positive family history of PD (control group) and a healthy control group of 15 subjects with a positive family history of sporadic PD (relative group) were investigated. For statistical analysis, the larger area of the two SNs echogenicity (aSNmax) of each individual was selected. Results: A significantly increased aSNmax was found for all subgroups compared with the control group. The group of homozygous carriers of a PINK1 mutation had a significantly increased aSNmax compared with all of the other subgroups, except the group of heterozygous mutation carriers. Conclusions: These findings in carriers of a PINK1 mutation are comparable with those in carriers of Parkin mutations and non-genetic PD. The increased aSNmax in family members without a mutation suggests an additional contributing factor independent of the PINK1 mutation that may also play a role in relatives of patients with sporadic PD.